Efficacy of fiber bands impregnated with Beauveria brongniartii cultures against the Asian longhorned beetle, Anoplophora glabripennis (Coleoptera: Cerambycidae) - Dubois, T.; Li, Z.; Jiafu, H.; Hajek, A.E. (Elsevier, 2004)
Use of 50 × 500 mm non-woven fiber bands impregnated with cultures of entomopathogenic fungi was investigated for control of Anoplophora glabripennis. Fungal bands produced as a commercial pest control product and obtained from industry contained Beauveria brongniartii NBL 851 while lab-produced bands contained B. brongniartii WU 20 or Metarhizium anisopliae VD 1. In the laboratory, adult longevity decreased when adult A. glabripennis were forced to walk for 5 s on bands impregnated with B. brongniartii NBL 851 and for 25 s on B. brongniartii WU 20 and M. anisopliae VD 1 bands. A field experiment was conducted over a 31-day period in Huaiyuan, Anhui, China, by attaching bands impregnated with B. brongniartii NBL 851 or WU 20 around the trunks of willows (Salix sp.) at two sites infested with A. glabripennis. Treatments were compared directly, by monitoring adult longevity, and indirectly, by counting oviposition scars and exit holes per tree to quantify relative oviposition per female. Adults collected from trees treated with B. brongniartii WU 20 died more quickly than adults from the trees treated with B. brongniartii NBL 851 or controls. At the site with higher A. glabripennis population densities, relative oviposition per female was significantly lower for both fungal treatments compared with the control treatment. Between fungal treatments, B. brongniartii NBL 851 had a 5 day earlier negative effect on oviposition per female than B. brongniartii WU 20.